Sojourn times in Jackson networks - Ferreira, Manuel Alberto M. (2013)
Jackson queuing networks have a lot of practical applications, mainly in the modelling of computation and telecommunications networks. Evidently the time that one customer - a person, a job, a message … – spends in this kind of systems, its sojourn time, is an important measure of its performance. In this work the practical known results about the sojourn time distribution are collected and presented.